(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
This research aims to determine the implementation of the Mobile JKN health service innovation at the Bantaeng Regency BPJS Health Office. The type of research used is qualitative with a descriptive type and data is collected using observation and interview techniques. The results of the research show that the implementation of the Mobile JKN innovation has not run optimally because application users have not reached all levels of society in order to provide quality services to the community. One of the unique features of the Mobile JKN application is the data change feature that is dominantly used and makes it easier for participants without needing to take care of administrative requirements at the BPJS Health Office. The quality of the Mobile JKN application can be seen by the large number of uses of the latest features, such as the online queue feature so that it can reduce the long queues that often occur at health facilities. The multi-functionality of the Mobile JKN application by providing more than 18 features makes it easier for participants to access services designed according to participant needs so that participants are comfortable in using the application.